Recent trends in replacement of disperser solvent in dispersive liquid-liquid microextraction methods. Issue 2 (3rd April 2019) - Sereshti, Hassan; Khorram, Parisa; Nouri, Nina
Abstract : Since its innovation in 2006, the dispersive liquid-liquid microextraction (DLLME) method has attracted the attention of analytical chemists in the field of sample preparation. This method has been successfully applied to determine trace amounts of pollutants in various matrices, but the restriction in the choice of suitable disperser and extraction solvents, and high disperser solvent consumption leading to decreased partition coefficients of the analytes between aqueous phase and extractant are its problems. To solve these drawbacks and develop environmentally friendly techniques, various alternatives for the conventional DLLME have been presented. The current review will begin with an introduction to the sample preparation, implementation of DLLME, and its advantages. Then, we focus on its drawbacks, which result mainly from the use of disperser solvent. Afterward, some of the most interesting approaches that have been employed and published until now are reviewed. Finally, an outlook on the future of these techniques will be given.